Polypropylene Fibers as Reinforcements of Polyester-Based Composites - Gonzalo Martínez-Barrera; Enrique Vigueras Santiago; Susana Hernández López; Osman Gencel; Fernando Ureña-Nuñez (International Journal of Polymer Science)
Effects of gamma radiation and the polypropylene fibers on compressive properties of polymer concrete composites (PC) were studied. The PCs had a composition of 30 wt% of unsaturated polyester resin and 70 wt% of marble particles which have three different sizes (small, medium, and large). The PCs were submitted to 200, 250, and 300 kGy of radiation doses. The results show that the compressive properties depend on the combination of the polypropylene fiber concentration and the applied radiation dose. The compressive strength value is highest when using medium particle size, 0.1 vol% of polypropylene fibers and 250 kGy of dose; moreover, the compressive modulus decreases when increasing the particle size.